Repetitive transcranial magnetic stimulation use in neuropathic pain with comorbid depression: a review of efficient treatment protocols’ parameters - D. S. Astafyeva; Ya. V. Vlasov; A. I. Strelnik; O. V. Chigareva; E. A. Markina; T. I. Shishkovskaya; D. A. Smirnova; A. Ya. Gayduk (Нервно-мышечные болезни)
Neuropathic pain affects 7 % of the general population worldwide, it is often resistant to analgesic treatments and is complicated with depressive states in 57–65 % of this patients’ cohort. Ongoing research of current therapeutic approaches, including repetitive transcranial magnetic stimulation (rTMS) use in neuropathic pain and depression, grants new data about the details of treatment protocols’ designs. The aim of our literature review was to evaluate those parameters of the treatment protocols which proved significant efficacy in the management of the neuropathic pain with comorbid depression.Focusing on the Scopus, Elsevier and PubMed databases search, we have found 639 peer‑review articles. 23 studies have been included into the data analysis, whereas others were excluded based on their heterogeneous study design. Across the data analysis we evaluated such rTMS parameters as the type of a coil, type of stimulation area, locus of gained evoked motor potential, amplitude of stimulation, duration of session, frequency/number of sessions per day/month, tie duration between sessions, number and frequency of trains, amount and frequency of pulses containing and efficacy of treatment. Those studies that performed repetitive transcranial magnetic stimulation using the figure‑of‑8 coil over the M1 brain area, for 10 or more daily sessions with duration from 7 up to 40 minutes, of 10–20 Hz frequency, intensity 80–90 % of resting motor threshold and total pulses number over 1500 per session demonstrated the greater efficacy in pain level decrease and depression scores reduction among neuropathic pain patients with comorbid depression. Conducting an additional maintenance phase of treatment prolonged the therapeutic effect of the course.Based on the data review, the parameters of the most efficient rTMS protocols’ designs in management of patients with neuropathic pain and comorbid depression have been revealed. Further research requires investigation of other promising indicators of rTMS efficacy use in neuropathic pain with comorbid depression, such as stimulation over multiple brain areas, the duration/timing of additional maintenance phase of treatment, and the figure‑of‑8 coil orientation options.